Silver Diamine Fluoride : A Caries "Silver-Fluoride Bullet" - Rosenblatt, A.; Stamford, T.C.M.; Niederman, R. (Journal of dental research, 2009)
The antimicrobial use of silver compounds pivots on the 100-year-old application of silver nitrate, silver foil, and silver sutures for the prevention and treatment of ocular, surgical, and dental infections. Ag+ kills pathogenic organisms at concentrations of < 50 ppm, and current/potential anti-infective applications include: acute burn coverings, catheter linings, water purification systems, hospital gowns, and caries prevention. To distill the current best evidence relative to caries, this systematic review asked: Will silver diamine fluoride (SDF) more effectively prevent caries than fluoride varnish? A five-database search, reference review, and hand search identified 99 human clinical trials in three languages published between 1966 and 2006. Dual review for controlled clinical trials with the patient as the unit of observation, and excluding cross-sectional, animal, in vitro studies, and opinions, identified 2 studies meeting the inclusion criteria. The trials indicated that SDF’s lowest prevented fractions for caries arrest and caries prevention were 96.1% and 70.3%, respectively. In contrast, fluoride varnish’s highest prevented fractions for caries arrest and caries prevention were 21.3% and 55.7%, respectively. Similarly, SDF’s highest numbers needed to treat for caries arrest and caries prevention were 0.8 (95% CI = 0.5–1.0) and 0.9 (95% CI = 0.4–1.1), respectively. For fluoride varnish, the lowest numbers needed to treat for caries arrest and prevention were 3.7 (95% CI = 3.4–3.9) and 1.1 (95% CI = 0.7–1.4), respectively. Adverse events were monitored, with no significant differences between control and experimental groups. These promising results suggest that SDF is more effective than fluoride varnish, and may be a valuable caries-preventive intervention. As well, the availability of a safe, effective, efficient, and equitable caries-preventive agent appears to meet the criteria of both the WHO Millennium Goals and the US Institute of Medicine’s criteria for 21st century medical care.